2021
DOI: 10.1002/hep4.1705
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy and Risk of Colorectal Cancer in Patients With Nonalcoholic Fatty Liver Disease: A Retrospective Territory‐Wide Cohort Study

Abstract: The benefit of colonoscopy and/or polypectomy for colorectal cancer (CRC) prevention in patients with nonalcoholic fatty liver disease (NAFLD) remains unclear. We aimed to estimate the incidence rate of CRC in patients with NAFLD who had and had not undergone colonoscopy. We conducted a retrospective territory-wide cohort study for patients aged over 40 years with NAFLD identified with the International Classification of Diseases, Ninth Revision, Clinical Modification codes between January 1, 2000, and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The definitions of hypertension, dyslipidemia, coronary heart disease, congestive heart failure, and cerebrovascular events were described in our previous studies and are also shown in the Supporting Information. [11,14]…”
Section: Definitionsmentioning
confidence: 99%
“…The definitions of hypertension, dyslipidemia, coronary heart disease, congestive heart failure, and cerebrovascular events were described in our previous studies and are also shown in the Supporting Information. [11,14]…”
Section: Definitionsmentioning
confidence: 99%
“…In our study, FLD was consistently associated with CRC risk in the presence or absence of liver fibrosis, suggesting that the risk of CRC development may be elevated even in a mild form of FLD without progression to advanced fibrosis. The significant association between FLD and incident CRC has important implications for CRC screening strategies, as demonstrated in a study by Zhang et al( 31 ), where patients with NAFLD who had not undergone colonoscopy exhibited a higher CRC risk than the general population, whereas those who had undergone colonoscopy evidenced a lower risk. We also found that MAFLD was associated with a higher risk of CRC even in the subgroup of youngest age (40–44 years), which is below the recommended CRC screening age ( 32 ).…”
Section: Discussionmentioning
confidence: 98%
“…CDARS is an electronic health care database that covers patients’ demographics, death, diagnoses, procedures, drug prescription and dispensing history, and laboratory results from all public hospitals and clinics in Hong Kong, which covers ~80% of the local population. [ 9 ] International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) coding was used in CDARS. When validated against a review of consultation notes and radiological and laboratory reports, the diagnosis of NAFLD by ICD‐9‐CM coding had a positive predictive value of 98.4%, and the diagnosis of cirrhosis complications had a positive predictive value of 85.7% and a negative predictive value of 95.9%.…”
Section: Methodsmentioning
confidence: 99%